2015 37th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2015
DOI: 10.1109/embc.2015.7319163
|View full text |Cite
|
Sign up to set email alerts
|

Real-time transmission of panoramic images for a telepresence wheelchair

Abstract: Abstract-This paper proposes an approach to transmit panoramic images in real-time for a telepresence wheelchair. The system can provide remote monitoring and assistive assistance for people with disabilities. This study exploits technological advancement in image processing, wireless communication networks, and healthcare systems. High resolution panoramic images are extracted from the camera which is mounted on the wheelchair. The panoramic images are streamed in real-time via a wireless network. The experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…In the modern world, innovations in telecommunications have made significant impacts on human modern life and offered numerous applications in daily life. However, the use of advanced telecommunication technologies to develop solutions for improving healthcare such as tele-monitoring, social interaction, and remote healthcare assistance through a wheelchair for people with disabilities is limited due to its technical challenges [1].…”
Section: Introductionmentioning
confidence: 99%
“…In the modern world, innovations in telecommunications have made significant impacts on human modern life and offered numerous applications in daily life. However, the use of advanced telecommunication technologies to develop solutions for improving healthcare such as tele-monitoring, social interaction, and remote healthcare assistance through a wheelchair for people with disabilities is limited due to its technical challenges [1].…”
Section: Introductionmentioning
confidence: 99%
“…Our research group has recently demonstrated a telepresence wheelchair based on the Internet protocols and the Skype cross-platforms [3,7]. Our prior attempts have achieved some degrees of success in software and hardware development.…”
Section: Introductionmentioning
confidence: 99%
“…Motivated by the above observation, this paper proposes new development in emerging information technology for an assistive system for healthcare applications. Compared to the previous works [3,7], the current work invokes the novel video communication framework to improve the performance of a telepresence wheelchair system further. More specifically, the aim of this study is to present a novel technical solution to the telepresence wheelchair system based on WebRTC for people with disabilities.…”
Section: Introductionmentioning
confidence: 99%
“…A telepresence wheelchair is a system that allows a person to control the wheelchair without actually being there. The telepresence wheelchair has attracted increasing attention from academia, industry, society, and so on, but technical challenges remain to improve the telepresence wheelchairs [1].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, spherical cameras have been introduced for a 360degree view. These have been previously explored in academic research projects for telepresence with a full view [1]. It has been proven that the solution for telepresence systems with a spherical camera is feasible.…”
Section: Introductionmentioning
confidence: 99%